A meta-analysis synthesizing the species sensitivity of fishes to the acute toxicity effects of pyrethroids - Habla II, Joseph Benjamin O. (Department of Biology and Environmental Science, College of Science, University of the Philippines Cebu, 2022)
Pesticide exposure has been known for some time now to have impacts on the ecosystem and fish health. Despite the potential to control pests, a couple of pesticides like pyrethroids can have deleterious impacts on organisms. The global use of pyrethroids has contaminated surface waters and this has led to the need for studies that determine the sensitivity of fishes. This meta-analysis aimed to profile the information availability from the selected pyrethroid pesticide. I also intended to establish a baseline understanding of the toxic effects of commonly used pyrethroids in tropical fishes. Based on 50% mortality at 96-h exposure, I pooled data sets and constructed a Species Sensitivity Distribution (SSD) and Hazardous Concentration of 5% of the fish species (HC5). The meta data produced and analyzed in the current review give baseline information of selected pyrethroids critical for regulatory organizations. The meta data also illustrate that available data on toxicity are lacking for some of the leading pyrethroids investigated. Moreover, these SSD comparisons illustrated differences in the level of toxicity of pyrethroids to fishes. Deltamethrin and cyhalothrin with an HC5 of 0.170 and 0.198 respectively, were the most toxic to fish, and temperate species with an HC5 of 0.444 were more vulnerable compared to tropical species. This highlights that there is a clear sensitivity of several fish species. I have also shown that lethal concentration 50 extrapolation from ecotoxicological tests with common test species from temperate regions would undervalue the actual consequence of pyrethroids in tropical marine ecosystems. Hence, results suggest that there is a need for more ecotoxicological research that uses tropical fishes to evaluate the ecological risk of pyrethroid pollution.